2010
DOI: 10.1097/01.nnr.0000313506.22722.53
|View full text |Cite
|
Sign up to set email alerts
|

"Stars" Aligned for Evidence-Based Practice

Abstract: A successful EBP program requires (a) consistent long-term vision and support from senior leadership; (b) resources such as trained personnel, finances, and time; and (c) structured approach to create an environment that facilitates the process. However, the success of an EBP program relies heavily on each nurse's commitment to change designed to improve nursing care for patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…Participants identified that nurses have important questions that need to be answered and the value of nursing research to health services is not comprehensively understood. Consistent with other research, however, a Nursing Research Internship program overcame self-imposed limitations felt by nurses ( Mark et al., 2020 ; Wells et al., 2007 ; Selig and Lewanowicz, 2020 ).…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…Participants identified that nurses have important questions that need to be answered and the value of nursing research to health services is not comprehensively understood. Consistent with other research, however, a Nursing Research Internship program overcame self-imposed limitations felt by nurses ( Mark et al., 2020 ; Wells et al., 2007 ; Selig and Lewanowicz, 2020 ).…”
Section: Discussionsupporting
confidence: 70%
“…Participants in this study reported that organisational support of nursing research was key, as identified in other research studies ( Stutzman et al., 2016 ). The literature reports on various approaches to engaging clinical nurses in research ( Mark et al., 2020 ; Wells et al., 2007 ; Selig and Lewanowicz, 2020 ; Olive et al., 2020 ), whether by a research partner organisation, a conjoint researcher or nurse researcher employed within the health service. ( Mark et al., 2020 ; Olive et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations